Pertumbuhan ekonomi sebagai variabel intervening dalam mempengaruhi tingkat kemiskinan provinsi di Pulau Sumatera dan Jawa - Rahmadi, Selamet; Nurjanah, Rahma (Jurnal Paradigma Ekonomika, 2022)
This study aims to measure the direct, indirect and total effect of HDI, population growth and unemployment rate on the poverty rate with economic growth as an intervening variable in the Provinces of Sumatra and Java. HDI, population growth and the unemployment rate directly have a positive/negative and significant/insignificant effect on the poverty rate and economic growth in the Provinces of Sumatra Island and Java Island. Indirectly, the influence of HDI through economic growth on the poverty level is the largest number with a positive and significant effect found in nine provinces on the island of Sumatra and Java. In total, the effect of economic growth on poverty is the largest number with a negative effect found in fifteen provinces on the island of Sumatra and Java.